Byung-Chul Han Goes to the Movies: Phenomenology of Relations with the World in Der Himmel über Berlin (1987) - Botero-Bernal, Andrés; Aguirre-Román, Javier Orlando; Almeyda-Sarmiento, Juan David (Estudios de Filosofía, 2025)
In this paper we show how the film Der Himmel über Berlin (Wenders, 1987) allows for a phenomenological reflection on the bonds of human beings with the world. We submit the hypothesis that the thinking of Byung-Chul Han, functions as a philosophical lens through which such a reading may be advanced. This paper has three sections: the first sees Damiel, one of the film’s main characters, as a vehicle to describe the light-ness of the world and the angst resulting from not being able to bond with the weight of existence. The second presents Peter Falk as the main trigger that causes Damiel to decide to enter the world of mortals and live a life exiled from eternity. Finally, we pres-ent Marion, Damiel’s romantic interest, as the main motivation for Damiel to renounce being an angel, as she fulfills the role of an Eros capable of triggering in the individual the vital strength to cause the subject to enter into a bond with the world.